Vibration Characteristics of Capped Viscous Damping Based on Frame Restoring-Force Amplitude - Mogi, Yoshihiro; Nakamura, Naohiro; Nabeshima, Kunihiko; Ota, Akira (Frontiers in Built Environment, 2022)
This study investigates the performance of several capped viscous damping models which give an upper limit to the initial-stiffness-proportional damping force. The comparing capped viscous damping models are the original and newly proposed one. The original capped damping model is expected to have a certain degree of frequency insensitiveness. However, unless the damping force reaches the capped value, the damping may be simply behaving as the initial-stiffness-proportional damping, also there is no clear physical basis for setting the capping value. Conversely, it is confirmed that the newly proposed damping model improves the original model problems faced with setting the capping value and frequency insensitiveness accuracy. In this study, the discussion is primarily focused on structural engineering using a 20-story fish bone model comprising a steel and reinforced concrete, but this argument can be applied to various engineering fields such as civil and mechanical engineering. Especially, this proposed model does not have mass term damping, it may effective for a large nonlinear analysis such as sliding /uplifting and base-isolated structure.